2005
DOI: 10.1007/s10620-005-1606-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hepatic Artery Chemotherapy on Viral Hepatitis in Patients With Hepatocellular Carcinoma

Abstract: Transcatheter arterial chemoembolization (TACE) or arterial Yttrium-90 (90Y) microspheres are used to treat unresectable hepatocellular carcinoma (HCC), but little is known about their effects on viral hepatitis. The aim of this study was to determine their effect on viral hepatitis in patients with HCC. We carried out a retrospective review of patients treated for HCC. Worsening of viral hepatitis was determined by serum chemistry and viral loads where available. Fifty-two patients treated with TACE were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Some case reports also showed that TACE represents a major risk factor for HBV reactivation in HBV‐related HCC patients 10,19,20 . However, different or even controversial results were observed in other reports 11–14 . A prospective study showed that a single session of TACE had little effect on the incidence of HBV reactivation, and usually the HBV reactivated patients recovered spontaneously 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports also showed that TACE represents a major risk factor for HBV reactivation in HBV‐related HCC patients 10,19,20 . However, different or even controversial results were observed in other reports 11–14 . A prospective study showed that a single session of TACE had little effect on the incidence of HBV reactivation, and usually the HBV reactivated patients recovered spontaneously 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of thirteen studies (Salem et al 2011;Carr et al 2010;Kooby et al 2009;Lewandowski et al 2009;Lee et al 2008;Hou et al 2006;Kirchhoff et al 2006;Ahmad et al 2005;Cao et al 2005a, b;Liu et al 2005;Du et al 2002;Hao et al 2000) were included in our analysis criteria, which included 597 and 1,233 HCC patients for treatment with microsphere embolization and chemoembolization, respectively (Table 1). Of these published studies, ten had comparison data on response rate and 1-year survival rate, three had overall survival (OS), and two had time to progression.…”
Section: Studies Included In This Meta-analysismentioning
confidence: 99%
“…Thus, if these two subgroups were combined, the statistically significant difference was only marginal (RR 1.04 vs. 1.41, interaction P = 0.075). Data on ten studies were available for response rate analyses in 396 and 1,033 patients treated with microsphere embolization or chemoembolization, respectively (Carr et al 2010;Kooby et al 2009;Lewandowski et al 2009;Lee et al 2008;Hou et al 2006;Kirchhoff et al 2006;Ahmad et al 2005;Cao et al 2005a, b;Du et al 2002;Hao et al 2000). Overall, 231 (58.3%) and 570 (55.2%) patients who underwent microsphere embolization or chemoembolization showed complete or partial responses.…”
Section: Studies Included In This Meta-analysismentioning
confidence: 99%
“…found that there was no significantly increase of serum HBV‐DNA level in 52 HCC patients undergoing TACE. Another previous study found that TACE decreased HBV‐DNA level in primary liver cancer patients, especially for those with preoperative HBV‐DNA level of ≥ 1 × 10 5 /mL, and those with postoperative AFP decline. According to the EASL (2012) clinical guideline: Management of chronic hepatitis B virus infection , for HBeAg‐positive patients, treatment should be considered if the HBV‐DNA is > 20 000 IU/mL with ALT ≥ 2 ULN.…”
Section: Discussionmentioning
confidence: 90%
“…reported 69 cases of HCC with HBV infection that a single TACE would not increase serum HBV‐DNA level. Ahmad J et al . found that there was no significantly increase of serum HBV‐DNA level in 52 HCC patients undergoing TACE.…”
Section: Discussionmentioning
confidence: 99%